Uniting the Rio Conventions: Aligning action in 2024 for food Security UNCBD, UNFCCC and UNCCD. CGIAR Issue Brief Series for Informing COP 29 | Number 1. - Mukherji, Aditi; Bowa, Emma; Crichton, R.; Majdalani, R.; Masso, Cargele; Stapleton, James (CGIAR Climate Change Impact Platform, 2024)
The three Rio Conventions: aligning actions The 1992 Earth Summit in Rio gave rise to three intrinsically linked conventions on biodiversity, climate change, and desertification - now known as the three Rio Conventions. The Convention on Biological Diversity (CBD) focuses on the conservation of biological diversity, its sustainable use, and the fair and equitable sharing of benefits arising out of genetic resource use. The Convention to Combat Desertification tackles desertification and the effects of land degradation and drought towards land degradation neutrality. The Framework Convention on Climate Change sets the overall intergovernmental framework to tackle climate challenges within a specific timeframe, to allow ecosystems to adapt, enable economic development and ensure food security.